Relationship between pregnant women with anaemia of maternal age at risk and low birth weight in a social security hospital in Peru: Relación entre gestantes con anemia en edad materna de riesgo y bajo peso al nacer en un hospital de la seguridad social del Perú - Luna, José Luis Villalva (2020)
Introduction: Anemia and low birth weight are very important public health problems. Objective: To determine the association between anemia in pregnant women with risk maternal age and low birth weight in the Obstetrics-Gynecology service of the Guillermo Almenara Irigoyen Hospital, in the period from October to December of the year 2018. Methods: A study of non-experimental, retrospective, cross-sectional, analytical, case-control type. In the period from October to December 2018, a total of 312 pregnant women with maternal age at risk (teenage and elderly pregnant women) were registered, of which 72 were anemic (Hb <11 g / dl), being the number of cases, and in order to improve statistical power, the relationship between cases and controls of 1: 2 was established, with the number of controls or non-anemic pregnant women with risk maternal age 142. The general characteristics are analyzed by group of anemic pregnant women and non-anemic, and its association with risk maternal age. The association of anemia in separately pregnant adolescents and elderly women with low birth weight is determined by Chi-square test and Odds ratio. Results: Among the variables studied anemic pregnant women, the highest frequency of nulliparity and vaginal delivery, and the lowest frequency of a history of abortion and adequate prenatal control. Teenage pregnant women with anemia were not associated with an increased risk of low birth weight (p = 0.056). Pregnant women who were anemic were associated with a 6-fold increased risk of low birth weight (95% CI: 2,219 to 18,026; p = 0.000). Conclusions: Elderly pregnant women have a higher risk of presenting products with low birth weight.